Critical care ultrasound: development, evolution, current and evolving clinical concepts in critical care medicine - Su, Jing; Tie, Xin; Wei, Ying; Zhou, Ran; Zou, Tongjuan; Qin, Yao; Zeng, Xueying; Li, Yi; Yin, Wanhong (Frontiers in Medicine, 2025)
Critical care ultrasound (CCUS) has emerged as a vital tool in modern critical care medicine (CCM), revolutionizing the assessment and management of critically ill patients. CCUS provides real-time insights into patient conditions and enables physicians to analyze the underlying mechanisms and pathophysiology of critical illnesses based on established theories and clinical needs, ultimately visualizing the phenotypes of patients and guiding clinical practice. The innovations of wearable ultrasound and the incorporation of artificial intelligence are further reshaping and broadening its application. This review underscores the importance of CCUS as an integral component of CCM, highlighting its development, current applications, and future directions. In addition, questions are raised regarding the standard training and guidelines of CCUS needing to be addressed in the near future.